Optimalisasi Harga Penjualan Perumahan dengan Metode Goal Programming (Studi Kasus: Golden Gindi Residence Kota Bima Nusa Tenggara Barat) - Rahmawati, Lilik Ika; Gandhiadi, G. K.; Asih, Ni Made (Jurnal Matematika; Vol 3 No 2 (2013), 2022)
This research aims to determine the minimum selling price of each type of house using the method of goal programming, so that the developer  get profit  in appropriate with the targets set. Goal Programming method is one of the method of solving linear programming to solve the problems that include multiple targets. The result of the research showed: (1) the minimum salling price type of house 36/150 is Rp. 56.371.450,-; (2) type 45/150 is Rp. 77.261.250,-; (3) type 52/150 is Rp. 84.221.445,56. To calculate monthly installment purchase of a home within 5 years and 10 years using Capital Recovery Factor (CRF) method with annual interest of 11.5%. In order to obtain the amount of monthly loan installments within 5 years with 60 time installments for the type 36/150 is Rp. 930.250 , type 45/150 is Rp. 1.275.000 and type 52/150 is Rp. 1.389.800. By using the same method obtained the amount of monthly installments within 10 years with 120 installments for the type 36/150 is Rp. 549.900, type 45/150 is Rp. 815.300 and type 52/150 is Rp. 888.800 . Optimal selling price obtained was lower than the selling price from the developer, so the developer need to consider again the results obtained for the salling price of homes. The calculation of credit installments depending on the amount of interest and repayment period, so not become burden for the customers.
Keywords: real estate; Selling Price of house; Optimal Selling Price; Goal Programming; Capital Recovery Factor